Reestructuración comercial administrativa de la empresa comercializadora CYMA S.A.S (2018)
In the present work, the administrative commercial restructuring was carried out in the company Comercializadora CYMA SAS, which is a Colombian company dedicated to the commercialization of products and supplies for the chemical industry, in order to determine the current situation of the same and be able to generate improvement actions that improve business and administrative processes. Various tools were applied in order to diagnose the current situation of the company, evidencing the strengths, weaknesses, opportunities and threats that come from the activity of the company, in order to determine the strategies that best benefit the organization. The "restructuring, had as it took place in the commercial and administrative area of the company, was developed during a period of six months, in order to change the empirical method that is currently carried out where the main interest of the company has been to achieve the fulfillment of commercial goals and customer satisfaction, which is why the internal structure of the company has been affected, without carrying out the correct documentation of the processes, such as function manuals and adjustment of salaries that contribute to the remuneration of the employees.